Electron inelastic mean free path in water. Issue 40 (2nd July 2020) - Yesibolati, Murat Nulati; Laganá, Simone; Kadkhodazadeh, Shima; Mikkelsen, Esben Kirk; Sun, Hongyu; Kasama, Takeshi; Hansen, Ole; Zaluzec, Nestor J.; Mølhave, Kristian
Abstract : A nanochannel liquid cell was used to quantify the electron inelastic mean free path ( λ IMFP ) in water. The experimental values show large offsets from the generally accepted models, and can be used to determine the liquid thickness in a liquid cell. Abstract : Liquid phase transmission electron microscopy (LPTEM) is rapidly developing as a powerful tool for probing processes in liquid environments with close to atomic resolution. Knowledge of the water thickness is needed for reliable interpretation and modelling of analytical studies in LPTEM, and is particularly essential when using thin liquid layers, required for achieving the highest spatial resolutions. The log-ratio method in electron energy-loss spectroscopy (EELS) is often applied in TEM to quantify the sample thickness, which is measured relative to the inelastic mean free path ( λ IMFP ). However, λ IMFP itself is dependent on sample material, the electron energy, and the convergence and divergence angles of the microscope electronoptics. Here, we present a detailed quantitative analysis of the λ IMFP of water as functions of the EELS collection angle ( β ) at 120 keV and 300 keV in a novel nanochannel liquid cell. We observe good agreement with earlier studies conducted on ice, but find that the most widely used theoretical models significantly underestimate λ IMFP of water. We determine an adjusted average energy-loss term E m, water, and characteristic scattering angle θ E, water that improve the accuracy. The results provide a comprehensive knowledge of the λ IMFP of water (or ice) for reliable interpretation and quantification of observations in LPTEM and cryo-TEM studies.